Analysis of the Study of the Impact of Reproductive Health on Young Women Who Perform Elopements (Menik) in the Gayo Community, Central Aceh Regency, Indonesia: A Phenomenological Study - Apriani, Widya; Nova Ratna Dewi; Sri Wahyuni.MS (HM Publisher, 2024)
Introduction: Elopement (menik) is a traditional wedding tradition in the Gayo community, Central Aceh. This tradition often involves young women who are not physically and mentally ready to marry and have children. This research aims to analyze the impact of reproductive health on young women who elope (menik) in the Gayo community, Central Aceh Regency, Indonesia, using a phenomenological approach. Methods: This research was conducted using qualitative phenomenological methods. Data was collected through in-depth interviews with 15 young women who eloped (menik) and 5 key informants. Data were analyzed using thematic analysis techniques. Results: Research findings show that elopement (menik) has a negative impact on the reproductive health of Gayo young women. These negative impacts include: Poor reproductive health: Young women who elope (menik) are at greater risk of experiencing pregnancy and childbirth complications, reproductive tract infections, and sexually transmitted diseases. Pregnancy and childbirth at a young age: Young women who elope (menik) generally become pregnant and give birth at a young age, which can endanger the health of the mother and baby. Lack of access to reproductive health services: Young women who elope (menik) are often prevented by stigma and social norms from accessing reproductive health services. Conclusion: Elopement (menik) has a significant negative impact on the reproductive health of Gayo young women. Preventive efforts must be made to reduce the number of elopements (menik) and increase adolescent girls' access to education and reproductive health services.